Advanced therapeutics in focal and segmental glomerulosclerosis. (8th October 2018) - Liu, Yunzi; Shi, Yifan; Ren, Rong; Xie, Jingyuan; Wang, Weiming; Chen, Nan
ABSTRACT: Focal segmental glomerulosclerosis (FSGS) is a glomerulonephritis with podocyte injury. The renal prognosis of FSGS is relative poor. The overall remission rate of the FSGS patients with nephrotic syndrome to immunosuppressive treatments was reported as 47–66%, highlighting its therapeutic challenge—lacking in sufficient evidence‐based interventions. In first‐line treatment of nephrotic syndrome, daily oral prednisolone is a commonly used drug, whereas optimal treatment strategies, like indications and duration, remain controversial. Calcineurin inhibitor and cyclophosphamide are recommended in steroid‐dependent/steroid‐resistant patients. However, the high unmet need in effective immunosuppressive treatments calls for the development of new therapy methods. Rituximab, a monoclonal antibody targeting CD20 B‐cells, could increase the complete or partial remission rate, and decrease the relapse rate based on several previous studies on FSGS. In addition, the using of rituximab could potentially help the FSGS patients to stop the concomitant therapy include steroid and immunosuppressive agents. Other treatment options like adalimumab or abatacept also showed potential therapeutic effect, but still required larger Randomized Controlled Trial study to determine its efficiency and safety. Besides, expanding understanding of the genetic basis of FSGS is necessary to investigate new therapeutic agents. With the unsatisfied patients' outcome under the current treatments, innovation should be encouraged on the treatment strategy based on Kidney Disease: Improving Global Outcomes guideline and international collaborations are required for the potential novel immunosuppressive or immunomodulatory therapies. Summary at a Glance: In this systematic review of advanced FSGS therapeutics, the author summarized current evidences on the treatment FSGS and shared their experience. More prospective studies may pave the way to improve patient care in FSGS.